2000
DOI: 10.1046/j.1365-2672.2000.01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility testing: accurate and reproducible minimum inhibitory concentration (MIC) and non-inhibitory concentration (NIC) values

Abstract: Measuring the minimum inhibitory concentration (MIC) of a substance by current methods is straightforward, whereas obtaining useful comparative information from the tests can be more difficult. A simple technique and a method of data analysis are reported which give the experimentalist more useful information from susceptibility testing. This method makes use of a 100‐well microtitre plate and the analysis uses all the growth information, obtained by turbidometry, from each and every well of the microtitre pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
381
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(394 citation statements)
references
References 11 publications
10
381
0
3
Order By: Relevance
“…Nevertheless, the 10 5 spores/mL concentration showed the lowest variation in most of the cases. The MIC and the NIC of ZnO against P. expansum were determined as they are basic requirements for studying the antimicrobial activity of preservative agents and biocides (Lambert and Pearson 2000). It is demonstrated that the updated version of the LPM (Lambert and Lambert 2003) can be used to process the data obtained from the turbidimetric assay for successfully estimating the MIC and the NIC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the 10 5 spores/mL concentration showed the lowest variation in most of the cases. The MIC and the NIC of ZnO against P. expansum were determined as they are basic requirements for studying the antimicrobial activity of preservative agents and biocides (Lambert and Pearson 2000). It is demonstrated that the updated version of the LPM (Lambert and Lambert 2003) can be used to process the data obtained from the turbidimetric assay for successfully estimating the MIC and the NIC.…”
Section: Resultsmentioning
confidence: 99%
“…The updated version (Lambert and Lambert 2003) of the Lambert–Pearson model (LPM) based on a Gompertz function (Lambert and Pearson 2000) was then used to model the observed fractional areas: …”
Section: Calculation (Quantitative Assessment Of the Inhibitory Concementioning
confidence: 99%
“…Antimycobacterial activities of the compounds were performed by Center of Tuberculosis Antimicrobial Acquisition and Coordinating Facility (TAACF) at Southern Research Institute [36][37][38] .…”
Section: Microbiologymentioning
confidence: 99%
“…The data from Table 1 illustrate that all tested indolizine with phenanthroline skeleton have a good solubility in microbiological medium, which is quite promising from the pharmacological properties point of view. Then, the IC 50 , IC 90 and MIC of compound were determined by measuring bacterial growth after 5 days in the presence of test compounds [36][37][38]49 . The obtained results are listed in Table 1.…”
Section: Chemistrymentioning
confidence: 99%
“…Os dados foram ajustados ao modelo matemático descrito pela equação de Gompertz. 101 Os valores da concentração inibitória mínima (MIC) e concentração não inibitória (NIC) foram determinados calculando-se a área fracional sob a curva em função do logaritmo das concentrações dos controles positivos. A área fracional (A fracional ) sob a curva é definida como…”
Section: Padronização Do Ensaio E Triagem Fenotípica De X Albilineansunclassified